2006
DOI: 10.1038/ja.2006.12
|View full text |Cite
|
Sign up to set email alerts
|

New Aminophenoxazinones from a Marine Halomonas sp.: Fermentation, Structure Elucidation, and Biological Activity

Abstract: The addition of anthranilic acid to the culture medium of the marine derived Halomonas sp. strain GWS-BW-H8hM completely altered the secondary metabolite pattern relative to the standard conditions. The red-orange color of the culture filtrate extract was the result of the production of 2-aminophenoxazin-3-one (1), chandrananimycin C (5) and three new derivatives of 1 with a previously unknown substitution pattern: 2-amino-, 2-amino-8-benzoyl-, and 2-amino-8-(4-hydroxybenzoyl)-6-hydroxyphenoxazin-3-one (2ϳ4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 13 publications
(19 reference statements)
2
39
0
Order By: Relevance
“…Interestingly, Sphingobacterium has previously shown thioglucosidase activity [28] and recently α-glucosidase has also been reported from a strain of Halomonas [29]. In fact, many Halomonas species are reported in literature with varied activity, for example, a marine derived Halomonas strain produced certain antimicrobial and cytotoxic compounds with the addition of anthranilic acid in the fermentation medium [30]. Our study is also the first to report very strong glucosidase inhibition activity in a chromium resistant species of Leucobacter from the sponge Aka coralliphaga .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Sphingobacterium has previously shown thioglucosidase activity [28] and recently α-glucosidase has also been reported from a strain of Halomonas [29]. In fact, many Halomonas species are reported in literature with varied activity, for example, a marine derived Halomonas strain produced certain antimicrobial and cytotoxic compounds with the addition of anthranilic acid in the fermentation medium [30]. Our study is also the first to report very strong glucosidase inhibition activity in a chromium resistant species of Leucobacter from the sponge Aka coralliphaga .…”
Section: Resultsmentioning
confidence: 99%
“…and very few studies have been reported so far. Marine bacterial strain GWS-BW-H8hM was reported to inhibit growth of HM02 (gastric adenocarcinoma), HepG2 (hepatocellular carcinoma) and MCF7 cell lines and induce apoptosis via cell cycle arrest [29]. Highly heterogeneous polymers i.e.…”
Section: Discussionmentioning
confidence: 99%
“…No cytotoxic properties against the tumor cell lines HM02 (stomach), HepG2 (liver) and MCF7 (breast) tested could be observed up to a concentration of 10 µg/mL. [15] Even as a well-known terrestrial fungus, the genus Chaetomium is able to produce a remarkable variety of chemical diverse metabolites, e.g. chaetomin, [16] chaetoglobosins, [17] chaetoquadrins, [18] oxaspirodion, [19] chaetospiron [20] and the orsellides.…”
Section: Discussionmentioning
confidence: 99%